Experimental study of charging a compact PCM energy storage device for transport application with dynamic exergy analysis. (15th September 2019) - Nie, Binjian; She, Xiaohui; Yu, Qinghua; Zou, Boyang; Zhao, Yanqi; Li, Yongliang; Ding, Yulong
Highlights: The charging performance of a thermal energy storage device is studied. The device has a maximum charging rate at 1.3 kJ/s. The charging thermal efficiency can reach 87%. The charging exergy efficiency can reach 70%. The optimal charging depth was obtained. Abstract: Thermal energy storage is essential whenever there is a mismatch between the supply and consumption of energy. When the air conditioning system is applied in transport, a great challenge occurred due to frequent fluctuations of cooling load which causes comfort degradation and even healthy concern. In this study, we evaluate charging performance including charging time, transient charging rate, overall energetic and exegetic efficiency of the designed device under different operating conditions. Evolutions of PCM temperature with processing time both in the axial and radial directions are also investigated. What's more, the dynamic exergy efficiency is studied for the first time to assess the optimal charging depth and charging time. The experimental results show that the charging time can be reduced by 49% and 28% by dropping the charging temperature from 15 to 11 °C and increasing the inlet air velocity from 0.70 to 1.20 m/s. The designed energy storage device has flexible charging rates with the maximum value of 1.3 kJ/s, high thermal efficiencies at 87% and overall exergy efficiencies up to 70%. Both the drop of the inlet air temperature and the rise of the inlet air velocity contribute to the energy efficiency. The analysis of dynamic exergy efficiency shows that the maximum exergy efficiency can reach around 90% with the optimal charging time varying from 10 to 52 min. The corresponding optimal charging depth varies between 46% and 58% under the studied conditions. These findings could provide guidelines for the design and optimization of PCM energy storage device specifically when it is used in the transport field.